2014
DOI: 10.1007/s13730-014-0155-9
|View full text |Cite
|
Sign up to set email alerts
|

New-onset systemic lupus erythematosus in a long-term hemodialysis patient with acute pleuritis and pneumonitis

Abstract: A 61-year-old woman, with a 25-year history of maintenance hemodialysis due to end-stage renal disease of unknown causes, was admitted because of systemic joint pain and inflammatory response of unknown etiology that persisted for 1 month. Laboratory data on admission revealed leukocytopenia, lymphocytopenia, high serum C-reactive protein, and positivity for antinuclear antibody (ANA) and anti-double strand DNA. After admission, she progressively developed cough and dyspnea. A chest radiograph revealed bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Several cases of new-onset SLE after dialysis initiation have been reported previously. [5][6][7][8] Hiyamuta et al 8 reported a 61-year-old woman who developed SLE 25 years after the initiation of dialysis. She presented with arthritis and pleuritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cases of new-onset SLE after dialysis initiation have been reported previously. [5][6][7][8] Hiyamuta et al 8 reported a 61-year-old woman who developed SLE 25 years after the initiation of dialysis. She presented with arthritis and pleuritis.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Thus, only a few cases of new-onset SLE during maintenance dialysis therapy have been reported. [5][6][7][8] Here, we report a rare case of a 61-year-old woman who newly developed SLE with serositis, including pleuritis, peritonitis, and pericarditis, 4 years after the introduction of hemodialysis for end-stage renal disease.…”
Section: Introductionmentioning
confidence: 99%